Dual-Plane versus Prepectoral Breast Reconstruction in High–Body Mass Index Patients. Issue 6 (June 2020) - Gabriel, Allen; Sigalove, Steven; Storm-Dickerson, Toni L.; Sigalove, Noemi M.; Pope, Nicole; Rice, Jami; Maxwell, G. Patrick
Abstract : Background: Breast reconstruction in patients with a high body mass index (BMI) (≥30 kg/m 2 ) is technically challenging and is associated with increased postoperative complications. The optimal reconstructive approach for these patients remains to be determined. This study compared outcomes of prepectoral and dual-plane reconstruction in high-BMI patients to determine whether there was an association between postoperative complications and the plane of reconstruction. Methods: High-BMI patients who underwent immediate dual-plane or prepectoral expander/implant reconstruction were included in this retrospective study. Patients were stratified by reconstructive approach (dual-plane or prepectoral), and postoperative complications were compared between the groups. Multivariate logistic regression analysis was performed to determine whether the plane of reconstruction was an independent predictor of any complication after adjusting for potential confounding differences in patient variables between the groups. Results: Of 133 patients, 65 (128 breasts) underwent dual-plane and 68 (129 breasts) underwent prepectoral reconstruction. Rates of seroma (13.3 percent versus 3.1 percent), surgical-site infection (9.4 percent versus 2.3 percent), capsular contracture (7.0 percent versus 0.8 percent), and any complication (25.8 percent versus 14.7 percent) were significantly higher in patients who had dual-plane versus prepectoral reconstruction ( p < 0.05). Multivariate logistic regression identified dual-plane, diabetes, neoadjuvant radiotherapy, and adjuvant chemotherapy as significant, independent predictors of any complication ( p < 0.05). Dual-plane reconstruction increased the odds of any complication by 3-fold compared with the prepectoral plane. Conclusion: Compared with the dual-plane approach, the prepectoral approach appears to be associated with a lower risk of postoperative complications following immediate expander/implant breast reconstruction and may be a better reconstructive option in high-BMI patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.